The Impact of Murottal Therapy, Eye Masks, and Earplugs on Sleep Quality in Intensive Care Unit Patients at a Tertiary Hospital - Suryani, Lili; Sastra, Lenni (Frontiers on Healthcare Research, 2025)
Background: Patients in the ICU often experience poor sleep quality. The consequences of poor sleep quality include cognitive and mood disturbances, decreased immune function, and cardiovascular issues. Typically, pharmacological management for poor sleep quality involves the use of sedative medications. However, sedatives can cause side effect, such as altering sleep physiology and potentially prolonging mechanical ventilation. Therefore, additional non-pharmacological therapy is needed, such as combining murrotal therapy with the use of eye masks and earplugs this study aims to determine the impact of murottal therapy, eye masks, and earplugs on sleep quality in intensive care unit patients at a tertiary hospital. Methods: The study utilized a pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 17 ICU patients at Dr. M. Djamil General Hospital in Padang, Indonesia selected through accidental sampling. Data were collected from May 6 to June 9, 2024, using the Richards-Campbell Sleep Questionnaire (RCSQ). Data analysis included both univariate and bivariate analysis, with the bivariate analysis conducted using the Paired T-Test.   Results: The results showed that the mean sleep quality score before and after the intervention was 32.59 and 78.00, respectively. There was a significant effect of combining murottal therapy with eye masks and earplugs on sleep quality in ICU patients (P < 0.001). Conclusion: It is recommended that hospitals adopt the combination of murottal therapy with eye masks and earplugs as a standard procedure to enhance sleep quality in ICU patients.